Unexpected Cyclization During the Mitsunobu Reaction of d-Talose Derivatives - Chuang, Huei-Lin; Sawant, R. C.; Luo, Shun-Yuan (Synlett, 2013)
A d-talose derivative underwent unexpected cyclization during a Mitsunobu reaction. A plausible pathway for the reaction involves an attack of the nucleophilic azide on the benzyl ring by intramolecular cyclization with loss of the benzyl group. These newly formed, unexpected compounds may be used in the synthesis of derivatives of C-nucleosides.
Keywords: Mitsunobu reaction; tetrahydroxy-LCB; d-talose; nucleosides; cyclization